Hemoglobin variants with electrophoretic mobility similar to hemoglobin S - Miranda, Armandina (2017)
Hemoglobinopathies are among the most common inherited diseases around the world and are one of the world’s major health problems. They are monogenic diseases of autosomal recessive transmission resulting from mutations affecting the genes responsible for the synthesis of globin chains. Abnormal hemoglobins (Hb), named Hb variants, are caused by structural defects resulting from an altered amino acid sequence in globin chains, being Hb S the more frequent and pathogenic/disease associated. The aim of this work was to identify and characterize Hb variants with mobility similar to Hb S when using common laboratorial methodologies, such as isoelectric focusing and high pressure ion exchange chromatography (HPLC). Hemoglobin analysis was performed by isoelectric focusing and HPLC. Globin chain variants were classified in alpha or beta type by reversed phase high performance chromatography. Hb S was confirmed by the solubility test. In order to identify the rare Hb variants, molecular analyses were performed in patient’s DNA. From 2010 to 2016, in the routine practice of our laboratory, 601 cases of variants of Hb were detected with mobility Hb S-like. Amongst them, 433 were confirmed as being Hb S (72.0%). Others hemoglobins also with clinical relevance, Hb D and Hb Lepore, were prevalent, 90 (15.0%) and 61 (10.2%), respectively. The remaining 17 cases were classified as rare (2.8%) and 10 of them were identified by molecular studies as: Hb Maputo (1), Hb G-Coushata (1), Hb Summer Hill (1), Hb Setif (1), Hb G Waimanalo (1), Hb D Iran (1) Hb Oleander (1), Hb Ottawa (1), Hb Etobicoque (1) and Hb Matsue-Oki (1). Hb Matsue-Oki was found in compound heterozygosity with the –α3.7kb-thalassemia deletion. We can conclude that combining the results obtained by the different biochemical methodologies allow the presumptive identification of the more prevalent variants, namely Hb S, Hb D and Hb Lepore, and direct the molecular study for the definitive identification. This study also revealed that several rare variants have similar mobility as Hb S and, consequently, some safety measures should be applied in order to achieve their accurate identification. A correct laboratorial diagnosis is essential for proper patient’s clinical management and genetic counselling.